COMPARATIVE EFFICACY OF LIFETIME METHODS OF RABBIT PASSALUROSIS LABORATORY DIAGNOSTICS - Khorolskyi, A. (Scientific Progress & Innovations, 2021)
The main methods of diagnostics in veterinary parasitology are laboratory methods of research, many of which involve the detection and differentiation of the pathogen. Various diagnostic methods based on mod-ern scientific achievements and the accumulated experience of practitioners are used for various parasi-toses. It is known that in order to diagnose most helminthiases, coproscopic examination of feces is used, based on the detection of parasite eggs using flotation, sedimentation or combined methods. However, la-boratory diagnostics of rabbit passalurosis includes the examination of scrapings from the body anal area, which is connected with the cycle of helminth development, and the study of feces at this invasion is ineffec-tive. The aim of the research was to establish the effectiveness of the existing lifetime methods of Passalurus ambiguus laboratory diagnostics. Experimental studies were conducted at the Laboratory of the Department of Parasitology and Veterinary Sanitary Expert Examination of Poltava State Agrarian University and in the conditions of individual farms of Poltava region. The testing of three methods of rabbit passalurosis lifetime laboratory diagnostics with the use of glycerin, adhesive tape and flotation was conducted. The main indica-tor of diagnostic efficacy of each method was the value of the infection intensity. According to the results of the research, it was established that the most sensitive method of lifetime laboratory diagnostics of rabbit passalurosis was the method of examining the body anal area using adhesive tape. By this method, 80 % of infected rabbits were revealed. Glycerin and Fulleborn’s methods showed lower sensitivity, where 60 and 25 % of infected rabbits were detected, respectively. The high diagnostic efficacy of the method with the use of adhesive tape has been proven by the intensity of the infection indicators. According to this method, on the average, 5.94 eggs of passalurises were revealed, which is 3.4 and 4.9 times more in comparison with the method of using glycerin and Fulleborn’s method. The obtained data of the experimental researches allow to recommend the method with the use of adhesive tape as the most effective and ergonomic method of lifetime laboratory diagnostics of rabbit passalurosis.